Vibrational Spectroscopic Study of 1H-1,2,4-Triazole Hofmann-Td-Type Complexes - Bayrak, Celal (Asian Journal of Chemistry, 2010)
Hofmann-Td-type modified hosts containing 1H-1,2,4-triazole molecule attached to M(II) tetracyanocadmate frame, with a given formula: M(Htrz)2M'(CN)4, where M = Mn; M' = Zn, Cd or Hg; M = Cd, M' = Cd or Hg; Htrz = 1H-1,2,4-triazole, have been synthesized. Their elemental analyses, FT-IR (4000-400 cm-1) and the FT-Raman spectra (4000-50 cm-1) are reported for the two [Cd(Htrz)2Cd(CN)4 and Cd(Htrz)2Hg(CN)4] of these complexes. All the vibrational modes of coordinated Htrz are characterised. The spectral features of the compounds studied are found to be similar to each other indicating that they have analogous structures.